DEVELOPMENT STAGES AND SPATIAL FORMATION OF RECREATIONAL AND HEALTH-REHABILITATION COMPLEXES - Kurbanova Dilnoza (TADQIQOTLAR, 2026)
Abstract This study examines the development stages and spatial formation of recreational and health-rehabilitation complexes, particularly in desert and semi-desert regions. The research highlights the transformation of such complexes from simple therapeutic environments into multifunctional spatial systems influenced by environmental, social, and technological factors. The findings demonstrate that climate-responsive planning, compact spatial organization, and bioclimatic design significantly improve environmental performance and user comfort